Influence of second metal incorporation on nickel-based unsupported catalysts for CO2 reduction (CO2-SR) Technology - Essounani-Mérida, Sofía; Molina-Ramírez, Sergio; Cortés-Reyes, Marina; Herrera-Delgado, María Concepción; Larrubia-Vargas, María Ángeles; Alemany-Arrebola, Luis José (Elsevier, 2025)
The incorporation of alkali or alkaline-earth metals in unsupported Ni-based catalyst was analyzed as a strategy for high-temperature CO2 storage and chemical regeneration via methane, within the framework of CO2 storage–regeneration (CO2-SR) technology. It was observed that the addition of Ba, Ca, Sr and K into the Ni-catalyst modifies not only the textural but also the electronic properties of the catalysts. A restructuring of the unsupported oxide surface occurs by the reduction of the modified Ni-oxide catalyst when exposed to a H2-atmosphere at high temperature (600 °C). Upon oxygen release from NiO lattice, the alkali metals favor the reduction and stabilization of these Ni-metallic species. In such a way, nickel-metallic particles are formed from the NiO-bulk, thus generating unsupported metal catalysts; stabilized by interaction with alkali metals and anchored on the surface. The presence of Ba, Ca, Sr or K in the Ni-based catalyst formulation influences the CO2 storage capacity and regeneration by conversion employing CH4 registering the trend Ca>Ba>K>Sr for the catalytic activity at 600 °C in term of CO2 removal capacity and CH4 conversion.
Keywords: Catálisis; Catalizadores; Metales alcalinoterreos; Gases de efecto invernadero - Reducción; CO2-SR technology; CO2 storage; CH4 regeneration; Ni-M bimetallic unsupported catalyst; Ba, Ca, K or Sr